2021
DOI: 10.3390/life11020169
|View full text |Cite
|
Sign up to set email alerts
|

HBV/HDV Co-Infection: Epidemiological and Clinical Changes, Recent Knowledge and Future Challenges

Abstract: Several investigations have been published on Hepatitis Delta Virus (HDV) infection in recent years, from which we have drawn the salient data to provide readers with useful information to improve their knowledge on the subject. HDV genotypes 5–8 have been recently imported to Western countries from central Africa, whose clinical relevance deserves further investigation. Ongoing HDV replication has been identified as an independent predictor of progression to cirrhosis and HCC for patients with HDV chronic hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 131 publications
0
22
0
Order By: Relevance
“…The response rates range from 17 to 47%, however, with high relapse rates 28–32 . Longer treatment duration with marketed PEG‐IFN alpha or combination with nucleos( t )ide analogues such as adefovir, lamivudine, or entecavir did not increase the response rates 33,34 . Bulevirtide recently received conditional approval by European Medicines Agency for the treatment of CHD based on phase 2 data 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rates range from 17 to 47%, however, with high relapse rates 28–32 . Longer treatment duration with marketed PEG‐IFN alpha or combination with nucleos( t )ide analogues such as adefovir, lamivudine, or entecavir did not increase the response rates 33,34 . Bulevirtide recently received conditional approval by European Medicines Agency for the treatment of CHD based on phase 2 data 35 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 , 31 , 32 Longer treatment duration with marketed PEG‐IFN alpha or combination with nucleos( t )ide analogues such as adefovir, lamivudine, or entecavir did not increase the response rates. 33 , 34 Bulevirtide recently received conditional approval by European Medicines Agency for the treatment of CHD based on phase 2 data. 35 The preliminary result of ongoing trials by adding PEG‐IFN showed better treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate is considerably lower than those obtained in another study, which found 0.98% (95%CI: 0.61%-1.42%) in the general population and 14.57% (95%CI: 12.93%-16.27%) in HBsAg-positive individuals [138] . However, there were concerns about the populations selected, the markers and the HBsAg prevalence estimates used in the latter study that may have introduced biases [139] .…”
Section: Hepatitis D Virusmentioning
confidence: 99%
“…Eight genotypes of HDV have been identified at present, distributed differently in the world: Type 1 is present worldwide and prevalent in western Europe and North America, type 2 mainly in the Far East, Egypt and Iran, type 3 in the Amazon Basin, type 4 in Japan and Taiwan, types 5 to 8 in Africa but now spreading also in Western regions due to immigration flows[ 4 ]. In Western countries, HDV infection at present occurs mostly in elderly adults with chronic HBV infection or in young immigrants from endemic areas[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic HDV infection is the most severe and rapidly progressive form of chronic hepatitis, leading to cirrhosis in 70% of patients within 5-10 years[ 7 ]. Furthermore, as compared with HBV mono-infection, HBV/HDV co-infection increases the risk up to three times of cirrhotic patients developing hepatocellular carcinoma[ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%